Normal anthropometry does not equal normal body composition in pediatric intestinal failure. Issue 1 (27th September 2021) - Yanchis, Dianna; Belza, Christina; Harrison, Debra; Wong‐Sterling, Sylvia; Kean, Penni; So, Stephanie; Patterson, Catherine; Wales, Paul W.; Avitzur, Yaron; Courtney‐Martin, Glenda
Abstract: Background: Published reports on abnormal body composition in pediatric patients with intestinal failure have been in patients with poor growth. The goal of the current study is to report the body composition of normally growing patients with intestinal failure. Methods: Children 8–18 years old with a dual‐energy x‐ray absorptiometry (DXA) between January 1, 2013, and July 15, 2018, were included in the study. Data were retrospectively collected from the medical charts and included demographics, residual bowel anatomy, nutrition support, height, and weight. DXA data, including total body less head bone mineral density (BMD), fat mass (FM), and fat‐free mass (FFM), were collected and compared with published literature controls matched for age and sex. Results: Thirty‐four children met inclusion criteria. Mean age at the time of DXA was 9.6 ± 1.8 years. Weight‐ and height‐for‐age z ‐scores were −0.4 ± 0.9 and −0.5 ± 1.0, respectively. Mean BMD z ‐score was −1.0 ± 1.3. Twenty‐six percent of patients (n = 9) had reduced BMD. Patients with intestinal failure had higher FM ( P = .02) and lower FFM ( P = .02) compared with controls. Conclusions: These data show that, despite reference range z ‐scores for height and weight, children with intestinal failure are at risk for abnormal body composition. Body composition should be routinely measured in children with intestinal failure to direct nutrition interventions.